NILAI-NILAI ISLAM DALAM RITUAL SEDEKAH LAUT NELAYAN TRITIH KULON KABUPATEN CILACAP - Is Ismah (STAI Sufyan Tsauri Majenang, 2021)
Islam was present in Indonesia, which later became the majority religion, which did not mean that the customs and traditions of the ancestors were abandoned. Making customs and traditions inherited from ancestors is simply abandoned. This is one form of evidence that tradition and religion are not mutually exclusive and that they are mutually sustainable. Tritih Kulon Village in Cilacap Regency is a coastal area whose residents are Muslims. The local residents are fishermen. The tradition of sea alms or larungan is also one of the traditions that is still guarded by fishermen in Tritih Kulon Village.Key Words: Islam, Sea Alms Ritual